EDUKASI DAN PENDAMPINGAN PENGGUNAAN MEDIA SOSIAL SECARA SEHAT MELALUI ELECTRONIC POCKETBOOK SEBAGAI SARANA PENDIDIKAN KESEHATAN REPRODUKSI PADA PELAJAR - Saputra, Meidi; Tama, Tika Dwi; Fauzi, Moh Fery; Wati, Ratu Suci Sholikhah; Ulandari, Sukma (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas Panca Marga Probolinggo, 2024)
The health world is no stranger to cases related to the adolescent reproductive system. The case is caused by a lack of knowledge about adolescents' reproductive system including the health of the reproductive organs. The purpose of this community service is to provide education as well as provide assistance to junior high school (junior high school) students to be wise in using social media and access platforms on social media as a means for reproductive health education for students. Partners in this service are students, teachers and principals of Muhammadiyah 1 Malang Junior High School. The method of implementing this community service consists of 1) analyzing the situation by conducting pre-service in the form of observation and initial interviews with service partners, namely the teacher council and several students related to the problems faced, 2) planning service activities that focus on education and mentoring, 3) implementation of community service and 4) Evaluation of service by conducting a reflection session on the achievements of the service team. The result of this community service is that the students of Muhammadiyah 1 Malang Junior High School get insights related to reproductive health so that they have readiness to face the dynamics of puberty. In addition, they are also expected to have a wise attitude in using social media. Keywords: Education, Electronic Pocketbook, social media, Mentoring, Reproduction